Organizing for Societal Grand Challenges. - Gümüsay, Ali Aslan; Marti, Emilio; Trittin-Ulbrich, Hannah; Wickert, Christopher (Bingley : Emerald Publishing Limited, 2022)
The ebook edition of this title is Open Access and freely available to read online. Organizing for Societal Grand Challengesunpacks how diverse forms of organizing help tackle-or reinforce-grand challenges,while emphasizing the need for researchers to expand their methodological repertoire and reflect upon scholarly practices.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books